Caracterização física e química de locais de ocorrência do açaizeiro(Euterpe aleracea, Mart) no Estado do Amapá e sua relação com o rendimento e qualidade do fruto2 - Gantuss, Carlos Alberto Ribeiro (2016)
This research was developed in Amapá State areas of natural ocurrence of ‘açaí’ palm trees (Euterpe oleracea, Mart.) in order to study the relationships between soil physical and chemical properties and fruit quality-yield. Soil samples were collected in the layers of 0- 10; 10-20; 20-30; 30-40 and 40-50 cm depth in areas of the following municipalities, soil position and geographic coordinates: Macapá, “Terra Firme”, 00º 07’ 03’’N, 51º 08’ 47’’ W; Mazagão, Lowland, 00º 02’ 33’’ S, 51º 15’ 24’’ W; and Amaparí, Hillslope, 00º 47’ 50’’ N, 51º 57’ 38’’ W, with soil textural classes of sandy clay loam, clay, and silty clay loam, respectively. Soil pH values of Hillslope and “Terra Firme” soils were classified as slightly acidic while the mean pH of Lowland soils was 5.6. Soil organic matter contents were higher in “Terra Firme” as compared to Hillslope soils and slightly superior to the Lowland soils. Sum of bases (SB) values were high in the Lowland due to the high levels of exchangeable calcium and magnesium, while Terra Firme soils showed high values of aluminum saturation compared to the other areas. Cation exchange capacity (CEC) values followed the trend: Lowland > “Terra Firme” > Hillslope. Lowland soils had the highest ‘açaí’ palm tree production with greater number of tillers (8.112 units/ha on average), tree mean diameter of 15.5 cm, annual average yield of 7.4 kg tree-1, and pulp/fruit yield of 25 %. Pulp pH values in the Lowland soils (5.2) was higher than in the plants growing in the two other soils: Hillslope (4.8) and “Terra Firme” (4.9), while for pulp ºBrix values the three sites had similar values (3.0-3.1). Sensorial analysis results indicated acceptance averages for ‘açaí’ pulp (84 % water diluted) from the three sites: “Terra Firme”, 83.3 %; Lowland, 87.8 %, and Hillslope, 76.9 %. Organoleptic properties of ‘açaí’ pulp with the higher acceptance (Lowland areas) had the influence of higher values of the following soil properties: pH, CTC, SB, and base saturation (V) and lower values of aluminum saturation, which indicates a better condition in soil fertility, higher soil microporosity and water retention in Lowland soils.